2023
DOI: 10.1002/jbm.b.35233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alginate scaffolds on bone healing in defects formed with drilling model in rat femur diaphysis

Abstract: Alginate (ALG) is a biocompatible and biodegradable polymer. Mechanical weakness is one of the main problems for the alginate-based scaffolds. Various plasticizer additives or modifications tested to improve the mechanical properties. In the presented study, ALG plasticized with triacetin (TA), and tributyl citrate (TBC) than tested on bone healing. In the presented study, the alginate modified with triacetin or tributyl citrate. In-vitro, and in-vivo efficiency of the scaffolds tested on bone tissue regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The researchers tested bone healing with ethyl triacetate and tributyl citrate plasticized alginate. In vivo studies have shown alginate and triacetate-modified scaffolds to have a growthpromoting effect on osteoblasts (Arslan et al, 2023). Alginate shows promise in bone tissue engineering and regenerative medicine, and it can also inform drug/growth factor delivery therapeutic strategies for diseases requiring specific drug/growth factor duration of action (Zhao et al, 2022).…”
Section: Application Of Seaweed Polysaccharides In Bone Regenerationmentioning
confidence: 99%
“…The researchers tested bone healing with ethyl triacetate and tributyl citrate plasticized alginate. In vivo studies have shown alginate and triacetate-modified scaffolds to have a growthpromoting effect on osteoblasts (Arslan et al, 2023). Alginate shows promise in bone tissue engineering and regenerative medicine, and it can also inform drug/growth factor delivery therapeutic strategies for diseases requiring specific drug/growth factor duration of action (Zhao et al, 2022).…”
Section: Application Of Seaweed Polysaccharides In Bone Regenerationmentioning
confidence: 99%